ASYMMETRIC CELLULOSE ACETATE MEMBRANES USED IN SEPARATION APPLICATIONS - Gabriela CIOBANU; Lidia FAVIER; Maria HARJA (Journal of Applied Life Sciences and Environment)
This work focused on the use of cellulose acetate polymer for the preparation of porous asymmetric membranes using a phase inversion process. These membranes were characterised by scanning electron microscopy, a bubble-point method and sorption measurements. The preparation method used induced membrane anisotropy. The capacity of the membranes in the removal of electrolyte (NaCl) from aqueous solution was investigated. A good retention of 58.6% and a high flux rate of 8.9 × 10–4 m/s using NaCl solution of 200 mg/L concentration were obtained by cellulose acetate membranes prepared with water as non-solvent. The results showed that the membrane performance was affected by the membrane structure, which was determined by the conditions of membrane preparation.